2020
DOI: 10.1177/1049732320976365
|View full text |Cite
|
Sign up to set email alerts
|

“We All Join Hands”: Perceptions of the Kangaroo Method Among Female Relatives of Newborns in The Gambia

Abstract: Family support is essential for kangaroo mother care (KMC), but there is limited research regarding perceptions of female relatives, and none published from West African contexts. In-depth interviews were conducted from July to August 2017 with a purposive sample of 11 female relatives of preterm neonates admitted to The Gambia’s referral hospital. Data were coded in NVivo 11, and thematic analysis was conducted applying an inductive framework. Female relatives were willing to support mothers by providing KMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Many previous studies have observed these same challenges, noting a need for behavior change among primary caregivers as well as sufficient social support to overcome such barriers. 9 , 12 , 14 , 26 The results from this study agree that social support and behavior change are essential for KMC success; however, this study also highlights the critical need for economic support. Parents face competing priorities that underpin the time-commitment barrier described so often.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Many previous studies have observed these same challenges, noting a need for behavior change among primary caregivers as well as sufficient social support to overcome such barriers. 9 , 12 , 14 , 26 The results from this study agree that social support and behavior change are essential for KMC success; however, this study also highlights the critical need for economic support. Parents face competing priorities that underpin the time-commitment barrier described so often.…”
Section: Discussionsupporting
confidence: 65%
“…9,11 Numerous studies have underscored the role of gender norms with respect to KMC engagement. 9,11,14 Parent experiences of postpartum medical conditions and navigating other time commitments have also proven to be impediments to KMC. 9 As the benefits of KMC are striking, advocates continue working to overcome implementation challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Involving other family members as alternative KMC providers may mitigate early maternal unavailability, as identified by HCW in this study and as per the eKMC trial in which 46% of the intervention arm received first KMC from a female relative (14). Female relatives are willing to support mothers in this role (36) and are influential newborn care decision makers in many African communities (37,38). Hence, involving female relatives, especially elders, in policy and programs may assist with delivery of this complex intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption system refers to the key actors involved in provision of the intervention and their interests, values and interactions (33). As both HCW and KMC providers (mothers and families) are important actors in this complex intervention (36), this theme was sub-divided to enable consideration of factors related to each actor.…”
Section: Adoption System (Health Care Workers and Kmc Providers)mentioning
confidence: 99%
“…Other challenges to providing prolonged KMC duration included mothers being absent due to maternal illness, post-caesarean section or delivery at another health facility. This is reflected in nearly half of our intervention arm receiving first KMC contact from a female relative (aunt/grandmother) and highlights the importance of family support for KMC [ 29 ]. The high proportion of twins (17% of our cohort were twins both enroled) may have also affected provision of prolonged KMC, due to the reticence of KMC providers to perform KMC with unstable twins simultaneously.…”
Section: Discussionmentioning
confidence: 99%